The Role of the Government of West Java in the Implementation of the New and Renewable Energy Program Based on the Glasgow Climate Pact - Zahidi, M. Syaprin; Al Ayubi, M. Solahudin (Jurnal Aspirasi, 2023)
Abstrak: COP26 yang dilaksanakan di Glasgow, Skotlandia telah mendorong komitmen negara-negara di dunia yang hadir pada pertemuan tersebut untuk merealisasikan ambisi dunia dalam menekan angka peningkatan suhu bumi di batas 1,5°C. Salah satu solusi yang digemakan pada pertemuan tersebut adalah transisi penggunaan energi menuju energi baru dan terbarukan (EBT). Dalam mewujudkan komitmen tersebut maka Indonesia perlu mengidentifikasi sebaran peran dan kontribusi pemerintah daerah agar dapat membantu pencapaian target RUEN (Rencana Umum Energi Nasional) melalui RUED (Rencana Umum Energi Daerah). Dengan menggunakan pendekatan deskriptif-kualitatif, penelitian ini bertujuan untuk menjelaskan bagaimana peran pemerintah Jawa Barat sebagai pemerintah daerah dalam implementasi Pakta Iklim Glasgow. Penelitian ini merekomendasikan kepada Dewan Perwakilan Rakyat Republik Indonesia (DPR RI) melalui fungsi pengawasan untuk mendorong distribusi peran pemerintah daerah dalam implementasi EBT melalui empat komponen penting: integrasi regulasi pemerintah pusat dan pemerintah daerah, penyederhanaan birokrasi antara pemerintah daerah dan pemerintah pusat dalam perwujudan EBT, optimalisasi distribusi anggaran dan pembiayaan EBT, serta optimalisasi screening dan monitoring implementasi EBT pemerintah daerah. Dengan demikian, keterlibatan peran pemerintah Jawa Barat dalam mendukung percepatan target RUEN pada implementasi program EBT dapat terwujud secara optimal. Abstract: COP26 in Glasgow, Scotland, has encouraged the commitment of the countries in the world that were present at the meeting to realize the world's ambitions in suppressing the increase in the Earth's temperature to the limit of 1.5°C. One solution echoed at the conference was transitioning from energy use to new and renewable energy (NRE). In realizing this commitment, Indonesia needs to identify the distribution of roles and contributions of subnational governments so that they can help achieve the RUEN (National Energy General Plan) target through RUED (Subnational Energy General Plan). Using a descriptive-qualitative approach, this study aims to explain the role of the West Java government as a subnational government in implementing the Glasgow climate pact. This study recommends to the Indonesian House of Representatives (DPR RI), through its oversight function, to encourage the distribution of the role of subnational governments in the implementation of new and renewable energy (NRE) through four essential components: integration of national and subnational government regulations, simplification of the bureaucracy between subnational governments and the national government in the realization of NRE, optimizing NRE budget distribution and financing, as well as optimizing screening and monitoring the implementation of NRE in subnational governments. Thus, the involvement of the role of the West Java government in supporting the acceleration of the RUEN target on the implementation of the NRE program can be realized optimally. .